2017
DOI: 10.1093/femspd/ftx037
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Achromobacter insolitus type strain LMG 6003T, a pathogen isolated from leg wound

Abstract: Achromobacter insolitus is a newly described, Gram-negative, small (1-2 mm long) and coccoid pathogen that has been isolated from leg wound. Due to its potential threat to human beings, the type strain of this species LMG 6003T was completely sequenced in this study. The genomic analysis revealed that the genome of LMG 6003T consists of one circular DNA chromosome of 6 492 697 bp with a GC content of 65.10%. The entire genome contains 6208 predicted coding genes, 61 tRNAs and 13 rRNA genes. Comparative genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, several of the predicted new efflux pump genes were located in opportunistic or pathogenic bacteria, e.g. Acinetobacter baumannii, Achromobacter insolitus, O. anthropi, Pandoraea pulmonicola and Burkholderia cenocepacia [66][67][68][69][70]. Among these, Acinetobacter baumannii is a notorious pathogen harbouring a wide range of mobile resistance genes against clinically relevant antibiotics, including tetracyclines [71].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several of the predicted new efflux pump genes were located in opportunistic or pathogenic bacteria, e.g. Acinetobacter baumannii, Achromobacter insolitus, O. anthropi, Pandoraea pulmonicola and Burkholderia cenocepacia [66][67][68][69][70]. Among these, Acinetobacter baumannii is a notorious pathogen harbouring a wide range of mobile resistance genes against clinically relevant antibiotics, including tetracyclines [71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Enterobacterales , we observed that environmental or commensal proteobacteria, such as C. kerstersii ( 32 , 33 ), A. insolitus ( 34 ), and B. hinzii ( 35 ), were abundant in both animals and humans and have been reported to be opportunistic agents colonizing humans. Microorganisms from distinct genera, such as P. stutzeri , Clostridium ventriculi , Faecalibacterium prausnitzii , and Bilophila wadsworthia , accounted for a proportion similar to those of some well-described antimicrobial-resistant species.…”
Section: Discussionmentioning
confidence: 96%
“…These various genes were investigated for their potential roles in biofilm development on other Achromobacter strains of A. insolitus and A. xylosoxidans (Table 1). These genes linked to biofilm development have been curated from Li et al, Nielsen SM et al (21)(22)(23).…”
Section: Bioinformatics Analysismentioning
confidence: 99%